Poetic Operations : Trans of Color Art in Digital Media - cárdenas, micha, 1977- (Book collections on Project MUSE., 2022)
"In Poetic Operations artist and theorist Micha Cárdenas considers contemporary digital media, artwork, and poetry in order to articulate trans of color strategies of safety and survival. Drawing on decolonial theory, women of color feminism, media theory, and queer of color critique, caÌrdenas develops a method she calls algorithmic analysis. Understanding algorithms as sets of instructions designed to perform specific tasks (like a recipe), she breaks them into their component parts, called operations. By focusing on these operations, Cárdenas identifies how trans and gender nonconforming artists, especially artists of color, rewrite algorithms to counter violence and develop strategies for liberation. In her analyses of Giuseppe Campuzano's holographic art, Esdras Parra's and Kai Cheng Thom's poetry, Mattie Brice's digital games, Janelle Monáe's music videos, and her own artistic practice, Cárdenas shows how algorithmic analysis provides new modes of understanding the complex processes of identity and oppression and the intersection of gender, sexuality, and race"--